Pengajian kesusasteraan Melayu baru - Hanapi Dollah (Universiti Kebangsaan Malaysia, 2005)
This article explore the development of modern Malay literature as a field of study in the Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia (UKM). It started with a few courses covering more or less most aspects af the literature such as prose genre, authors, literary theory and criticism, comparative and creative writing offered to the undergraduate students. The courses at that time could be considered as a minor part of the Malay studies program. The major parts of the program were Malay language and classical Malay literature. Modern Malay literature grew into a distinctive and full fledged field of study as more academic staff joined the then department and new courses were introduced, especially after the establishment of the Malay Letters Department. When the Department was replaced with the School of Malay Language, Literature and Culture in 2001, the field of study become a new program. If the development of the modern Malay literature of the last 35 years is viewed within the framework of the premise that it could promote Malay identity and generate Malay civilization at the global level as put forward by its founder, Syed Muhammad Naguib al-Atas, it can be said that the achievement is minimal. This field of study needs to reposition its policies and direction.